Electrode slurry and preparation method thereof, electrode pole piece, battery and electric device

By using the combination of CMC, SBR and acrylic copolymer binder in the lithium battery electrode slurry, the existing adhesive matching problem is solved, and the processing performance of the electrode slurry and the long cycle performance of the battery is significantly improved, achieving the demand for high-performance batteries.

CN119601579APending Publication Date: 2025-03-11GREE ALTAIRNANO NEW ENERGY INC
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411438775.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The binders of existing lithium batteries have matching problems in different lithium iron phosphate battery systems and negative electrode slurry preparation processes, resulting in poor slurry processing performance and battery electrochemical performance.

Method used

The combination of CMC, SBR and acrylic copolymer binder is used as the binder for the electrode slurry. By adapting with other components such as active materials, the processing performance of the electrode slurry and the long cycle performance of the battery are significantly improved.

Benefits of technology

Significantly improve the processing performance of electrode slurry, such as smooth screening of slurry, improving adhesion, reducing pole rebound, etc., while improving the long cycle performance of the battery to meet the needs of high-performance batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005085802480000051
    Figure BDA0005085802480000051
  • Figure BDA0005085802480000061
    Figure BDA0005085802480000061
  • Figure HDA0005085802490000011
    Figure HDA0005085802490000011
Patent Text Reader

Abstract

The invention relates to the field of batteries, and discloses electrode slurry, a preparation method thereof, an electrode plate, a battery and an electric device. The electrode slurry comprises an electrode active material, a conductive agent, a binder, a plasticizer and a solvent, the binder comprises CMC (Carboxymethyl Cellulose), SBR (Styrene Butadiene Rubber) and a water-based binder, the water-based binder is an acrylic copolymer binder, and the SBR is a styrene, butadiene and acrylonitrile copolymer binder. The CMC, the SBR and the specific water-based copolymer binder are combined and applied to the electrode slurry, through matching with other components such as an active material and the like, the processing performance of the electrode slurry can be remarkably improved, for example, smooth sieving of the slurry, improvement of binding power, reduction of pole piece rebound and the like can be achieved, and meanwhile compared with slurry adopting a commercial binder, the service life of the electrode slurry is prolonged, and the service life of the electrode slurry is prolonged. And the long cycle performance of the battery can be improved, and the requirement of a high-performance battery can be further met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular to an electrode slurry and a preparation method thereof, as well as an electrode plate, a battery and an electrical device. Background Art

[0002] The electrode slurry ratio of a complete lithium-ion battery generally includes active material, conductive agent, binder, solvent and additives. The binder plays the role of bonding the active material to the current collector, the active material to the active material, and the active material to the conductive agent. At the same time, it maintains the stability of the mechanical structure of the pole piece and the electrochemical performance of the battery during the production and use of the battery. Although the amount of binder used is small, its role is irreplaceable.

[0003] Polyacrylic acid (PAA) is a water-soluble high molecular polymer formed by the polymerization of acrylic acid monomers. Due to the presence of a large number of carboxylic acid groups in its structure, it can form a strong interaction with active substances and current collectors, thus having good bonding properties. It can also help form a stable SEI film during the cycle of lithium batteries, improving its cycle performance. It is also a green, high-performance, and sustainable binder. However, single polyacrylic acid is brittle under dry conditions, and active substances are prone to agglomeration during the pulping process, with poor dispersibility. General products are aqueous solutions.

[0004] At present, the binder of commercial lithium batteries is not a single-component binder, but is modified by polymerizing various functional monomers or blending other polymers to optimize various properties. However, different binders have matching problems in different lithium iron phosphate battery systems and negative electrode slurry preparation processes. Otherwise, the performance of the binder itself will not be brought into play, resulting in poor slurry processing performance and battery electrochemical performance. Therefore, it is very important to choose a suitable water-based binder. Summary of the invention

[0005] In view of this, the purpose of the present application is to provide an electrode slurry and a preparation method thereof, so that it can significantly improve its processing performance and improve the long cycle performance of the battery;

[0006] Another object of the present application is to provide an electrode sheet, a battery and an electrical device based on the above-mentioned electrode slurry.

[0007] In order to solve the above technical problems / achieve the above purposes or at least partially solve the above technical problems / achieve the above purposes, as a first aspect of the present application, an electrode slurry is provided, comprising an electrode active material, a conductive agent, a binder and a solvent; the binder comprises CMC, SBR and an aqueous binder, the aqueous binder is an acrylic copolymer binder, and the SBR is a styrene, butadiene, acrylonitrile copolymer binder.

[0008] Optionally, the mass ratio of the electrode active material, the conductive agent, CMC, the aqueous binder and SBR is (96.0-96.5%):(0.9-1.0%):(0.5-0.7%):(1.2-1.4%):(0.8-1.0%):0.4%.

[0009] Further optionally, the electrode slurry also includes a plasticizer, and the mass of the plasticizer is no more than 0.4% of the mass of the electrode active material; the electrode active material is a positive electrode active material or a negative electrode active material, and the positive electrode active material includes one or more of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, and a ternary material, and the negative electrode active material is one or more of graphite negative electrode materials; the conductive agent includes one or more of carbon black conductive agents, carbon nanotube conductive agents, conductive graphite conductive agents, graphene conductive agents, and carbon fiber conductive agents.

[0010] As a second aspect of the present application, a method for preparing the electrode slurry is provided, wherein an electrode active material, a conductive agent, a binder, and a plasticizer are mixed in proportion and prepared into the electrode slurry by wet stirring.

[0011] Optionally, the preparation method further comprises adding a plasticizer together with the electrode active material, the conductive agent and the binder by wet stirring.

[0012] As a third aspect of the present application, an electrode plate is provided, comprising a current collector and a dried slurry coated on a surface of the current collector, wherein the slurry comprises the electrode slurry described in the present application.

[0013] As a fourth aspect of the present application, a battery is provided, comprising the electrode plate described in the present application, a plate having a polarity opposite to that of the electrode plate described in the present application, a diaphragm and an electrolyte.

[0014] As a fifth aspect of the present application, there is provided an electrical device, comprising the battery described in the present application, wherein the battery provides electrical energy to the electrical device.

[0015] This application applies a combination of CMC, SBR and a specific aqueous copolymer binder in the electrode slurry. By adapting with other components such as active materials, the processing performance of the electrode slurry can be significantly improved, such as smooth screening of the slurry, increased adhesion, reduced electrode rebound, etc. At the same time, compared with the slurry using commercial binders, it can also improve the long cycle performance of the battery, which can further meet the needs of high-performance batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application.

[0017] Figure 1 Shown are the comparative results of the cycle performance of the soft-pack batteries prepared in Example 1, Comparative Example 1, and Comparative Example 2. DETAILED DESCRIPTION

[0018] The present application discloses an electrode slurry and a preparation method thereof, as well as an electrode plate, a battery and an electrical device. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all deemed to be included in this application. The products, processes and applications described in this application have been described through preferred embodiments. Relevant personnel can obviously modify or appropriately change and combine the products, processes and applications described in this article without departing from the content, spirit and scope of this application to realize and apply the technology of this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0019] It should be noted that, in this article, if relational terms such as "first" and "second", "step 1" and "step 2", and "(1)" and "(2)" appear, they are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "comprise", "include" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or equipment including the elements. At the same time, the embodiments in this application and the features in the embodiments may be combined with each other without conflict.

[0020] In view of the poor matching of existing commercial water-based copolymer binders in electrode slurry, which leads to insufficient processing performance of electrode slurry and battery cycle performance, in the first aspect of the present application, an electrode slurry is provided, including an electrode active material, a conductive agent, a binder and a solvent; the binder includes CMC, SBR and a water-based binder, the water-based binder is an acrylic copolymer binder, and the SBR is a styrene, butadiene, acrylonitrile copolymer binder. The electrode slurry of the present application includes water-based copolymer binders of different components, and the use of an acrylic copolymer binder and an SBR binder of CMC and a styrene, butadiene, acrylonitrile copolymer can effectively solve the matching problem of the current commercial water-based copolymer binder. In certain embodiments of the present application, the aqueous binder is commercially available Badfu A831, which is a copolymer binder formed by hydrolysis of acrylic acid as a monomer, and has a solid content of 6%; the SBR is commercially available Daoying GD1346L, which is a binder formed by copolymerization of styrene, butadiene, and acrylonitrile, and has a solid content of 40%; the CMC includes one or two of lithium carboxymethyl cellulose and sodium carboxymethyl cellulose.

[0021] In certain embodiments of the present application, the mass ratio of the electrode active material, the conductive agent, CMC, the aqueous binder, and SBR is (96.0-96.5%): (0.9-1.0%): (0.5-0.7%): (1.2-1.4%): (0.8-1.0%). In other embodiments of the present application, the mass ratio of the electrode active material, the conductive agent, CMC, the aqueous binder, SBR, and the plasticizer is 96%: 0.9%: 0.7%: 1.4%: 1.0%.

[0022] In certain embodiments of the present application, the electrode slurry also includes a plasticizer, and the mass of the plasticizer is no more than 0.4% of the mass of the electrode active material; the addition of the plasticizer can enhance the flexibility and plasticity of the electrode piece and reduce the cracking of the electrode piece. When adding more, the electrode active material will account for a smaller proportion and reduce the electrochemical performance. The plasticizer will evaporate when the electrode slurry is applied and will not affect the composition of the entire electrode electrochemical active layer. In other embodiments of the present application, the plasticizer is 1,3-butanediol.

[0023] In certain embodiments of the present application, the electrode active material is a positive electrode active material or a negative electrode active material; the positive electrode active material includes one or more of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, and a ternary material; the negative electrode active material includes one or more of graphite negative electrode materials, such as artificial graphite, natural graphite, etc. Artificial graphite includes mesophase carbon microbeads, soft carbon, and hard carbon, etc. depending on the preparation process.

[0024] In certain embodiments of the present application, the conductive agent includes one or more of carbon black conductive agent, carbon nanotube conductive agent, conductive graphite conductive agent, graphene conductive agent and carbon fiber conductive agent. Among them, carbon black conductive agent includes conductive carbon black SP, Ketjen black and acetylene black. The solvent includes but is not limited to water and N-methylpyrrolidone (NMP).

[0025] In some embodiments of the present application, the electrode slurry has a solid content of 50-54% and a viscosity of 2500-4500 mPa·s. Although the solid content of the slurry is relatively high, it can pass through a 180-mesh sieve smoothly. In other embodiments of the present application, the electrode slurry is a negative electrode slurry, and the negative electrode active material is graphite.

[0026] In the second aspect of the present application, a method for preparing the electrode slurry is also provided, wherein the electrode active material, the conductive agent, and the binder are mixed in proportion and stirred by a wet method to prepare the battery negative electrode slurry.

[0027] In certain embodiments of the present application, the preparation method further comprises adding a plasticizer together with the electrode active material, the conductive agent, and the binder by wet stirring.

[0028] In certain embodiments of the present application, the preparation method comprises:

[0029] The electrode active material, CMC and conductive agent are mixed uniformly according to a proportion; then a mixture of an aqueous binder and deionized water is added thereto twice, and dispersed uniformly after each addition, and a plasticizer and an NMP solvent are added at the same time during the second addition; finally, SBR is added to the above-mentioned uniformly dispersed slurry and continued to disperse and stir to obtain the electrode slurry.

[0030] In the third aspect of the present application, an electrode plate is provided, comprising a current collector and a dried slurry coated on the surface of the current collector, wherein the slurry comprises the electrode slurry described in the present application. In certain embodiments of the present application, the current collector comprises a metal foil, such as an aluminum foil, a copper foil, etc. After the electrode slurry is coated on the surface of the current collector, the solvent is evaporated by drying and rolled to obtain the electrode plate; in certain other embodiments of the present application, the electrode plate is a negative electrode plate, and after testing, the negative electrode plate has greater adhesion, lower resistivity, and smaller rebound.

[0031] As a fourth aspect of the present application, a battery is provided, comprising the electrode plate described in the present application, a plate having a polarity opposite to that of the electrode plate described in the present application, a diaphragm and an electrolyte. In certain embodiments of the present application, the battery is a lithium-ion battery, the electrode plate described in the present application is a negative electrode plate, and the active material of the positive electrode plate opposite thereto is lithium iron phosphate.

[0032] In certain embodiments of the present application, the electrolyte is a lithium hexafluorophosphate electrolyte, and the separator is a PP separator.

[0033] In certain embodiments of the present application, the battery includes but is not limited to a soft-pack battery, a button battery, a half-battery or a full battery, etc. In certain embodiments of the present application, the battery is a soft-pack battery, which is obtained by slicing, baking, welding, short-circuit testing, liquid injection, formation, aging, and capacity separation of the above-mentioned negative electrode sheet and the positive electrode sheet opposite thereto. According to the test of the present application, the soft-pack battery has a low gas production and a good cycle performance.

[0034] As a fifth aspect of the present application, an electric device is provided, comprising the battery described in the present application, wherein the battery provides electric energy for the electric device. The electric device may be various devices driven by the battery, including but not limited to electric vehicles, electric vehicles, self-balancing vehicles, flatbed vehicles, aircraft, lighting equipment, household appliances, etc.

[0035] In each group of comparative experiments provided in this application, unless otherwise specified, other experimental conditions, materials, etc. are kept consistent except for the differences indicated in each group, so as to provide comparability. The experimental materials and reagents used in the examples can be obtained from commercial channels unless otherwise specified.

[0036] The following is a further description of an electrode slurry and a preparation method thereof, as well as an electrode plate, a battery and an electrical device provided in the present application.

[0037] Embodiment 1:

[0038] The negative electrode slurry includes 96.0wt% of graphite, 0.7wt% of lithium carboxymethyl cellulose, 1.4wt% of Badfu A831, 1.0wt% of Daoying GD1346L, 0.9wt% of conductive carbon black, and an additional plasticizer of 0.4wt% of the mass of graphite.

[0039] Negative electrode sheet preparation: The above negative electrode slurry is coated on both surfaces of 6μm copper foil, and roller pressed after coating. The coating weight is 157g / m 2 , rolling thickness is 108±3μm;

[0040] Cell preparation: Use the above-mentioned positive electrode sheet as the positive electrode, the negative electrode sheet as the negative electrode, a lithium hexafluorophosphate electrolyte containing EC (24.5%), DMC (16.5%), EMC (41%), VC (2.5%), and LiPF6 (15.04%), and a 16μm PP separator to assemble a small soft-pack battery.

[0041] Comparative Example 1:

[0042] The preparation was carried out in accordance with Example 1, except that Badfu A831 was replaced with another commercially available PAA type aqueous binder, Indile LA136D, which is a sodium acrylate-acrylonitrile type polymer, the polymer is mainly composed of linear segments, and the solid content is 6%.

[0043] Comparative Example 2:

[0044] The preparation was carried out according to Example 1, except that Badfu A831 was replaced with another commercially available PAA-type water-based adhesive Tianci E300L, which is a modified PAN and PAA multipolymer, pre-neutralized with NaOH, has a solid content of 10%, and has the characteristics of low swelling and high adhesion.

[0045] Comparative Example 3:

[0046] Prepared with reference to Example 1, the difference is that Badfu A831 is replaced by another commercially available PAA type water-based adhesive Jiuchang F636, which is an acrylic ester multipolymer formed by the polymerization of other functional monomers (confidential by the merchant) introduced into acrylic acid monomers, with a solid content of 15%, and has the characteristics of low addition, high adhesion, low rebound and expansion; and Daoying GD1346L is replaced by Arkema HSV900, which is a styrene, butadiene, acid monomer copolymer emulsion with a solid content of 40%.

[0047] Since the replacement of the binder made it impossible to sieve through 180 mesh, subsequent processes could not be carried out, so there is no relevant experimental data for subsequent performance comparison.

[0048] Experimental example:

[0049] Comparing the processing performance and long cycle performance of Example 1 with the comparative examples, the results are shown in Tables 1 and Figure 1 ;

[0050] Table 1 Comparison of various processing performances

[0051]

[0052]

[0053] Note: The 48h slurry viscosity increase index measures the long-term stability of the active material in the fluid. The smaller the percentage, the more stable the slurry. Sedimentation means that the active material gradually sinks to the bottom and the slurry is unstable. The pole piece rebound phenomenon refers to the phenomenon that the thickness of the pole piece after a few hours in the actual battery production is thicker than the pole piece after rolling, and the rebound of the negative pole piece is the most obvious.

[0054] From the data in Table 1, it can be found that the binder selected in this application matches the slurry preparation process of this application, the slurry solid content is relatively high, about 50%, 180 mesh sieving is smooth, the slurry stability is good, the peeling strength is the best, and the 48h pole piece rebound is low, indicating that the electrode slurry has a high pole piece adhesion and cohesion, which can effectively prevent the active material and copper foil from falling off, and effectively inhibit the expansion of the pole piece during charging and discharging, further indicating its excellent processing performance. The other comparative examples used different types of binders for matching, and different degrees of performance degradation occurred in the four technical indicators, which fully demonstrated the matching factor of the binder in the slurry.

[0055] Depend on Figure 1 It can be found that after the small soft-pack battery has been cycled for 1000 cycles, the capacity retention rate of Example 1 is 98.62%, that of Comparative Example 1 is 95.68%, that of Comparative Example 2 is 96.52%, and there is no cycle data for Comparative Example 3 because no small soft-pack battery was made. This shows that the selection of the binder and the quality of the processing performance affect the cycle performance of the assembled small soft-pack battery. It also reflects that the binder matching of the present application has good elastic modulus and bonding force, and will not detach during long-term cycles due to the expansion of graphite caused by the continuous deintercalation of lithium ions; at the same time, the binder of the present application has good film-forming properties, can form a film on the graphite surface, and assist in the formation of an SEI film, thereby inhibiting further corrosion of the electrolyte and ensuring the stability of the graphite structure.

[0056] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. An electrode slurry, characterized in that: The invention comprises an electrode active material, a conductive agent, a binder and a solvent; the binder comprises CMC, SBR and a water-based binder, the water-based binder is an acrylic copolymer binder, and the SBR is a styrene, butadiene, acrylonitrile copolymer binder.

2. The electrode slurry according to claim 1, characterized in that: The mass ratio of the electrode active material, the conductive agent, CMC, the aqueous binder and SBR is (96.0-96.5%): (0.9-1.0%): (0.5-0.7%): (1.2-1.4%): (0.8-1.0%).

3. The electrode slurry according to claim 1 or 2, characterized in that: A plasticizer is also included, and the mass of the plasticizer is no more than 0.4% of the mass of the electrode active material.

4. The electrode slurry according to claim 1 or 2, characterized in that: The electrode active material is a positive electrode active material or a negative electrode active material. The positive electrode active material includes one or more of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, and ternary materials. The negative electrode active material is one or more of graphite negative electrode materials.

5. The electrode slurry according to claim 1 or 2, characterized in that: The conductive agent includes one or more of a carbon black conductive agent, a carbon nanotube conductive agent, a conductive graphite conductive agent, a graphene conductive agent and a carbon fiber conductive agent.

6. The method for preparing the electrode slurry according to claim 1, characterized in that: The electrode slurry is prepared by mixing the electrode active material, the conductive agent and the binder in proportion through a wet method.

7. The preparation method according to claim 6, characterized in that: The method also includes adding a plasticizer together with the electrode active material, the conductive agent and the binder through wet stirring.

8. An electrode plate, characterized in that: The invention comprises a current collector and a dried slurry coated on the surface of the current collector, wherein the slurry comprises the electrode slurry according to any one of claims 1 to 5.

9. A battery, characterized in that: It comprises the electrode plate as claimed in claim 8, a plate having a polarity opposite to that of the electrode plate as claimed in claim 7, a diaphragm and an electrolyte.

10. An electrical device, characterized in that: The battery according to claim 9 is included, and the battery provides electrical energy for the electrical device.

Citation Information

Cited By

  • Anode slurry dispersing, compacting and anti-cracking auxiliary agent for lithium battery and preparation method thereof

    CN121394408A

  • Phosphorus-carbon negative electrode aqueous slurry and preparation method thereof

    CN122025643A

  • Negative electrode binder, slurry, lithium-ion battery and its preparation method

    CN122563503A